PENGAWASAN BADAN PERMUSYAWARATAN DESA (BPD) TERHADAP KINERJA KEPALA DESA DALAM PEMBANGUNAN DESA KUALA SEMUNDAM KECAMATAN PETALANGAN KABUPATEN PELALAWAN TAHUN 2023 - Mulyani, Putri Cahaya; ,, Wazni (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This research is motivated by the essential role of the Village Consultative Body (BPD) in supervising the administration of village governance, particularly in ensuring that village development is carried out in accordance with planning and community needs. The problem addressed in this study is how the BPD exercises its supervisory function over the performance of the Village Head in the development of Kuala Semundam Village, as well as the factors that influence the effectiveness of that supervision. The purpose of this study is to identify and analyze the implementation of BPD’s supervisory role over the Village Head’s performance and the obstacles faced in its execution. This research uses a qualitative descriptive method, with data collected through interviews, observations, and documentation. The theoretical framework employed is Simbolon's theory of supervision, which includes internal, preventive, and repressive supervision in the execution of duties to achieve certain objectives. The results of the study indicate that the supervision carried out by the BPD over the Village Head’s performance is still not optimal. This is due to several factors, including supervision that is mostly limited to meetings without direct field observation, and a lack of understanding among BPD members regarding their supervisory functions and responsibilities. In addition, there are inhibiting factors such as limited time, inadequate resources, and a passive work culture. Therefore, there is a need to enhance the capacity and awareness of BPD members so that their supervisory role can be carried out more effectively in supporting the overall development of the village. Keywords : Development, Supervision, Village Consultative Body.